EFFORTS TO TEACHER GUIDANCE AND COUNSELLING IN UNDERSTANDING AND OVERCOMING STUDENTS PERSONALITY MELANCHOLY SENIOR HIGH SCHOOL 1 PADANGSIDIMPUAN ACADEMIC YEAR 2015-2016 - Rosnasari Marbun (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
Efforts Teacher of Guidance and Counseling In Understanding and Students Overcome Melancholy Personality. The importance of understanding and addressing the student teacher melancholy personality BK perform regulative, effective, and efficient as a contribution as the quality of BK at school. Where the research is done in Senior High School 1 Padangsidimpuan, namely the US and YRS as a student, teacher HLsebagai Mrs. BK, Mr. M.I.H as Headmaster. The purpose of this study was to determine Efforts Teacher of Guidance and Counseling to Address Melancholy personality of students at Senior High School 1 Padangsidimpuan the academic year 2015-2016 and for the students' understanding of Personality Melancholy in Senior High School 1 Padangsidimpuan the academic year 2015-2016. The method used is descriptive qualitative method. The data collection was done by using in-depth interviews (deep interview), observation and documentation. Processing data using qualitative narrative analysis. The results showed that the students do not understand what personality he had. Students do not know and understand what it is melancholy personality, and what it's like properties owned by the melancholy personality. BK teachers' efforts in understanding and overcoming melancholy personality is still limited to providing students the notion that teachers do preventive general. Effort BK is to give information services and individual counseling services. While the developmental efforts of the teacher BK other than in the form of information service, also in the form of student talent development and delivery of knowledge religion. Teachers BK is not fully able to give an understanding of personality melancholy. The lack of facilities and infrastructure owned by each school and the unavailability of special hours for teachers BK leave BK services to enter the classroom.